Konzo: from poverty, cassava, and cyanogen intake to toxico-nutritional neurological disease. - Hipólito Nzwalo; Julie Cliff (Public Library of Science (PLoS), 2011)
Konzo is a distinct neurological entity with selective upper motor neuron damage, characterized by an abrupt onset of an irreversible, non-progressive, and symmetrical spastic para/tetraparesis. Despite its severity, konzo remains a neglected disease. The disease is associated with high dietary cyanogen consumption from insufficiently processed roots of bitter cassava combined with a protein-deficient diet. Epidemics occur when these conditions coincide at times of severe food shortage. Up to 1993, outbreaks in poor rural areas in Africa contributed to more than 3,700 cases of konzo. The number of affected people is underestimated. From unofficial reports, the number of cases was estimated to be at least 100,000 in 2000, in contrast to the 6,788 cases reported up to 2009 from published papers.